KINERJA PARKIR DAN TINGKAT KEPUASAN PENGGUNA JASA LAHAN PARKIR PADA STASIUN KERETA API RAMBIPUJI (DAOP IX JEMBER) - Fadhil Aditya Putra Vidiyanto; Amri Gunasti; Irawati Irawati (Universitas Muhammadiyah Jember, 2019)
Infrastructure repair railway station was a special transportation infrastructure or separated by ground transportation network system to another. Train services badly needed community as economical transport compared with other transport. Rambipuji station is class II stations included in the operating Area IX Jember. At the train station in improving service required spatial or good facilities. Such as parking spaces for vehicles, a passenger waiting room, warehouse loading and unloading of goods as well as other facilities. The purpose of this research is to know the characteristics and performance of service knowing parking spaces Rambipuji station. In this research, to know the characteristics of parking in Rambipuji station is by using methods of observation and analysis calculation, while to know the level of satisfaction of parking lot users using Quisioner method Service Quality. In both these methods, all have a portion of its interests. The method of observation and analysis of calculations is used to know all the characteristics of parking available at Rambipuji station, while Quisioner Service Quality method is for the measurement of the preconception of users of parking Conducted by spreading Quisioner to 49 respondents to know the value of expectations and actual value of Performance received by train passengers Rambipuji.